2017
DOI: 10.1007/s40477-016-0234-1
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating palpebral grass awn in a dog

Abstract: An unusual case of a penetrating grass awn in an eyelid of a dog is reported. A 6-month-old mixed breed dog was referred to the Ophthalmology Unit of the Veterinary Teaching Hospital of Camerino University for anorexia, lethargy, left monolateral ocular swelling and pain to the left eye, present from 1 month. Ophthalmic examination of the left eye showed copious and purulent discharge, and ultrasonography revealed the presence of an abscess containing a grass foreign body. The grass awn was surgically removed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Ocular plant foreign bodies have been previously reported in dogs. [7][8][9][10] Within soft tissues, plant foreign bodies appear spindle shaped with two to three linear echogenic interfaces. An anechoic halo, due to accumulation of inflammatory fluid and soft tissue reaction surrounding the foreign body, is a common sonographic accompanying feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular plant foreign bodies have been previously reported in dogs. [7][8][9][10] Within soft tissues, plant foreign bodies appear spindle shaped with two to three linear echogenic interfaces. An anechoic halo, due to accumulation of inflammatory fluid and soft tissue reaction surrounding the foreign body, is a common sonographic accompanying feature.…”
Section: Discussionmentioning
confidence: 99%
“…One unusual case report described a dog with an intrapalpebral grass awn plant foreign body, resulting in an eyelid abscess. 9 Depending on its location within the conjunctiva, a foreign body may not be visible during routine ophthalmic examination. To date, periocular conjunctival plant foreign bodies identified with the aid of sonographic examination have not been reported in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…In a more general context, and based on litereature on injuries in animals as opposed to humans, our case exemplifies the difficulties of lack of anamnestic data and the bizzare mechanism and timing of corneal injury from this unsuspected metallic foreign body (sewing needle) in the orbit (Lavaud et al;Rose et al 2018.;Fische et al 2018;Fischer et al 2018.;Marchegiani et al 2017). It also shows that even given a lack of highly sophisticated diagnostic and surgical equipment, an adequate diagnosis and excellent surgical skill can lead to a good outcome for a patient with this rare type of problem.…”
Section: Resultsmentioning
confidence: 75%
“…However, a new finding of a triangular opacity in the cornea, stretching from a base at the limbus to the apex about 4 mm centripetally, was now visible. In the region of the opacity, there was also thickening of the cornea that was interpreted, due to the observation period, as corneal oedema or corneal oedema with slight infiltration rather than fibrosis (Kuhn et al 2002;Lavaud et al 2019;Marchegiani et al 2017;MacKay et al 2013).…”
Section: Case Presentationmentioning
confidence: 99%
“…Imaging techniques such as ultrasonography, computed tomography (CT) or MRI can be useful to identify and guide the removal of grass awns that have migrated into body tissues or cavities [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Recently, some authors have demonstrated the usefulness of transesophageal or transthoracic ultrasonography in identifying migrating grass awns within the thorax [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%